7-weeks of yoga training and its effects on flexibility and rate of force development in Olympic weightlifters - Ernst, A. T.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Pre- and post-testing was performed consisting of flexibility and rate of force development (RFD) measurements. Participants performed a sit and reach test followed by a loaded overhead squat test with a barbell that was recorded with video to assess joint angles. A countermovement jump and snatch were performed after to measure RFD. Afterwards the participants were split, with the experimental group receiving 7-weeks of yoga training. After 7-weeks participants returned for post-testing and there was a significant difference (p < 0.05) within participants for the following variables: sit and reach, shoulder flexion, knee flexion, ankle flexion, countermovement jump RFD, and snatch RFD. There was no significant interaction between the prelpost-test and the condition, or between groups for any variable (p r 0.05). Yoga training does not alter weightlifting performance variables.